(untitled) (Международный научный журнал «Инженер», 2026)
The article considers the task of automating the construction of a longitudinal profile of engineering water supply networks. A technique based on the use of geometric data of the pipeline route and hydraulic calculations is proposed. The software architecture includes modules for input of initial data, calculation of profile parameters and visualization of results. As part of the study, a program code was implemented that was used to perform a hydraulic calculation of the engineering network. The calculation of pressure losses is carried out using basic hydraulic formulas such as the Darcy–Weisbach equation. As an example, the calculation results for a typical water supply system are shown, demonstrated by a graph of pressure loss changes along the route of the water supply network. The developed software package simplifies and speeds up the calculations, which is confirmed by the analysis of the results.